Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms 2009
DOI: 10.1137/1.9781611973068.54
|View full text |Cite
|
Sign up to set email alerts
|

Biased Range Trees

Abstract: A data structure, called a biased range tree, is presented that preprocesses a set S of n points in R 2 and a query distribution D for 2-sided orthogonal range counting queries. The expected query time for this data structure, when queries are drawn according to D, matches, to within a constant factor, that of the optimal comparison tree for S and D. The memory and preprocessing requirements of the data structure are O(n log n). IntroductionLet S be a set of n points in R 2 and let D be a probability measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…High energy neutrinos have been extensively studied by the IceCube collaboration. 8 They have recently observed two double cascade events [60], consistent with ν τ . This would imply a neutrino flavor ratio ν e : ν µ : ν τ ∼ 1.05 : 1.35 : 0.6, consistent with 1 : 1 : 1 expected from a pion decay source after taking oscillations into account.…”
Section: Cosmic Raysmentioning
confidence: 79%
“…High energy neutrinos have been extensively studied by the IceCube collaboration. 8 They have recently observed two double cascade events [60], consistent with ν τ . This would imply a neutrino flavor ratio ν e : ν µ : ν τ ∼ 1.05 : 1.35 : 0.6, consistent with 1 : 1 : 1 expected from a pion decay source after taking oscillations into account.…”
Section: Cosmic Raysmentioning
confidence: 79%
“…A preliminary version of the results in the current paper have appeared in the Proceedings of the 20th ACM-SIAM Symposium on Discrete Algorithms (SODA 2009) [19]. Since then, Afshani et al [1] have discovered a general approach to distribution-sensitive geometric data structures that has many applications.…”
Section: New Resultsmentioning
confidence: 98%
“…Alstrup, Brodal, and Reuhe [4] further showed that range reporting in R 3 can be done with O(n log 1+ε n) space and O(log n + k) query time in the RAM model. More recently, Dujmović, Howat, and Morin [15] developed a data structure called a biased range tree which, assuming that 2-sided ranges are drawn from a probability distribution, can perform 2-sided range counting queries efficiently. Afshani, Barbay, and Chan [1] generalized this result, showing the existence of many instance-optimal algorithms.…”
Section: Prior Workmentioning
confidence: 99%
“…Range searching is a classic problem that has received much attention in the Computational Geometry literature (e.g., see [2,3,7,10,12,15,19,21,22,25]). In what is perhaps the simplest form of range searching, called orthogonal range reporting, we are given a rectangular, axis-aligned query range R and our goal is to report the points p contained inside R for a given point set, S.…”
Section: Introductionmentioning
confidence: 99%